Leadership in Nursing in Korea. - Myungsun Yi (Asian Pacific Island Nursing Journal, 2018)
Nurses are the largest workforce that impacts the health of the people. As the life expectancy and the number of people with chronic diseases increases in Asia, it is important for Asian nursing professionals to play a pivotal role in improving health status and quality of life by demonstrating their leadership. This article focuses on nursing leadership in Korea. Leadership exemplars were described in detail to show how successful nursing leaders set goals and challenged to meet these goals, despite numerous obstacles that exist in male-oriented society of Korea. And three essential elements that future nurse leaders should consider were suggested. First, awareness was emphasized as the first step to becoming a leader. Clear awareness about women and nursing would help nursing leaders reduce or eliminate gender biases that can undermine nurses' achievements and limit their advancement. Second, challenge was stressed as nursing leaders must challenge and expand the horizon of nursing by facing their situations and problems with courage. Lastly, transformation was highlighted, as the ultimate role of a leader is to make the world better. Four leadership frames--structural frame, human resource frame, political frame, and symbolic frame--were introduced to help guide their leadership journey to change the world. The results of this study would help nurses innovate with excellent leadership by efficiently managing nursing resources and by helping nursing organizations to adjust to changing demands in health care.